The reliability and validity of Lithuanian adaptive behavior scales: Pilot study results - Černiauskaitė, Dovilė (Psichologija, 2002)
This study examines some psychometric characteristics of Lithuanian adaptive behavior scales. Internal consistency coefficients for domains, ranging from 0,72 to 0,93, demonstrate acceptable level of reliability. The results from LAES pilot study revealed the increase of domain mean raw scores from one age to the next and some other age trends, what support the construct validity of the LAES as a development measure of adaptive behavior. The study of group differences on LAES results showed significantly and specifically different adaptive functioning of normal, visually handicapped, hearing impaired and mentally retarded children, what also supports the validity of the LAES.
Keywords: Lithuanian adaptive behavior scales